2005
DOI: 10.1128/aac.49.7.2716-2719.2005
|View full text |Cite
|
Sign up to set email alerts
|

New lnu (C) Gene Conferring Resistance to Lincomycin by Nucleotidylation in Streptococcus agalactiae UCN36

Abstract: Streptococcus agalactiae UCN36 was resistant to lincomycin (MIC ‫؍‬ 16 g/ml) but susceptible to clindamycin (MIC ‫؍‬ 0.12 g/ml) and erythromycin (MIC ‫؍‬ 0.06 g/ml).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 25 publications
(29 reference statements)
0
56
0
Order By: Relevance
“…Sequence analysis of the insert identified a gene whose product had 60% identity to LnuC from S. agalactiae (accession number AY928180). LnuC confers lincomycin resistance since it is a lincosamide nucleotidyltransferase that converts the antibiotic to a nontoxic form (5). The high level of sequence identity suggested that the pJIR2774 lincomycin resistance gene in C. perfringens strain 95-948, which we designated lnuP, conferred resistance by a similar mechanism.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Sequence analysis of the insert identified a gene whose product had 60% identity to LnuC from S. agalactiae (accession number AY928180). LnuC confers lincomycin resistance since it is a lincosamide nucleotidyltransferase that converts the antibiotic to a nontoxic form (5). The high level of sequence identity suggested that the pJIR2774 lincomycin resistance gene in C. perfringens strain 95-948, which we designated lnuP, conferred resistance by a similar mechanism.…”
Section: Resultsmentioning
confidence: 97%
“…tISCpe8, tISSag10 (4,5), and a putative element from Haemophilus parasuis have very similar genetic organizations (Fig. 3), and each element carries only two genes, a gene encoding a putative transposase and a lincomycin resistance gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that MTnSag1 (tISSag10) can be transferred by conjugation and that its acquisition by S. agalactiae might be efficient for the spread of lincomycin resistance since the majority of S. agalactiae strains possess Tn916-like genetic elements (Achard & Leclercq, 2007). However, the insertion of MTnSag1 (tISSag10) in the capsular operon of strain UCN36 has interrupted the cpsE gene; as a consequence the strain was non-typable (Achard et al, 2005). It is thus probable that gain of lincomycin resistance by strain UCN36 is concomitant with a reduction of its virulence.…”
Section: Mobile Genetic Element Of the Is1595 Familymentioning
confidence: 99%
“…The 1724 bp long mobilizable transposon MTnSag1 (also annotated MTnLnu) was found to be inserted within the cpsE gene belonging to the capsular synthesis operon of the S. agalactiae clinical strain UCN36 (Achard et al, 2005). MTnSag1 was reported to encode a transposase related to the InsAB' protein of IS1.…”
Section: Mobile Genetic Element Of the Is1595 Familymentioning
confidence: 99%